Complex Polymeric Architectures Self-Assembling in Unimolecular Micelles: Preparation, Characterization and Drug Nanoencapsulation - Stefania Ordanini; Francesco Cellesi (MDPI AG, 2018)
Unimolecular polymeric micelles are a class of single-molecule amphiphilic core-shell polymeric architectures, where the hydrophobic core is well stabilized by the hydrophilic shell, avoiding intermolecular core-core interactions. Multi-arm copolymers with a dendritic core, as well as hyperbranched and comb-like polymers, can form unimolecular micelles easily. In this review, examples of polymers able to form detectable unimolecular micelles will be presented, summarizing the analytical techniques used to characterize the unimolecular micelles and discriminate them from other supramolecular aggregates, such as multi-micelle aggregates. Unimolecular micelles are suitable for the nanoencapsulation of guest molecules. Compared to traditional supramolecular micelles, unimolecular micelles do not disassemble under dilution and are stable to environmental modifications. Recent examples of their application as drug delivery systems, endowed with increased stability and transport properties, will be discussed.